A intercompreensão de línguas românicas nas aulas de inglês: uma experiência inovadora nos cursos de Educação de Jovens e Adultos do Instituto Federal do Rio Grande do Norte - Oliveira, Janaina Michelle França de (2016)
It is undeniable that language teaching plays an important role in one’s life as Brazilian and international official documents affirm. The study of English language and anglphone cultures, or any other language, should promote a greater openness to different ways of structuring the world, as well as possibilities and opportunities to act critically in the world (PCNs, 1999). This research focuses on the Intercomprehension of Romance Languages (IRL) as a suggestion for the teaching and learning of the English language in the Young Adult and Adult Education Program (Educação de Jovens e Adultos - EJA) and aims to enhance learners’ potential to facilitate and motivate foreign language learning and self-perception. The involvement of the researcher to formulate and implement a plurilingual course was crucial to characterize the study as a Participatory Action Research (THIOLLENT, 2011; GRAY, 2012; FRANCO, 2005). Nine students of the Federal Institute of Rio Grande do Norte (IFRN)’s EJA participated in the study and did plurilingual activities involving four languages (Spanish, Italian, French and English) for a semester. The corpus of the research consists of quantitative and qualitative data collected through semi-structured questionnaires, audios, interviews, field notes, students’ plurilingual worksheet answers and verbal protocol (COHEN, 1996). In order to guide us in the formulation and execution of the plurilingual course and in the data analysis, we used, as a general theoretical framework for the teaching of foreign languages, the PCNs (1999), OCNs (2006), CEFR (2001) and FREPA/CARAP (2010). We also used the intercomprehension between related languages’ theoretical basis (DEGACHE, 2012; DOYÉ, 2005, 2007; ARAÚJO e SÁ, 2013; SANTOS, 2010; CAPUCHO, 2010; MELO; SANTOS, 2008; JAMET; SPITĂ, 2010; ESCUDÉ ; JANIN, 2010 CADDÉO; JAMET, 2013, among others) to support the research. As we sought to value the potential of learners through reading comprehension, we used the learning strategies categorized by O'Malley and Chamot (1995) and the theory of reading strategies and models (SOLÉ, 1998; Smith, 1999 KLEIMAN, 2013; PERFETTI 1999, 2007; ALONSO; MATEOS, 1985). The preparation and implementation of the plurilingual course, besides the theoretical support already mentioned, were also based on the sociointeractionist theory of Vygotsky (VYGOTSKY, 2007; BASTOS, 2014; OLIVEIRA, 1992), Krashen ‘s affective filter (1985, 2009), and meaningful learning theory (MOREIRA; MASINI, 2001; MOREIRA, 2010, 2011). Results suggest that to help students realize that their English language knowledge is meaningful, among other factors, they need to have greater autonomy and a less idealized notion of foreign language learning. The research also indicates that the linguistic proximity and the observation of the use of strategies in IRL contributed to the reading proficiency of texts in English, fomenting in learners a greater appreciation of their potential, and an increase self-confidence to understand texts in Romance languages, and in English, as well as, seemed to have contributed to changing students’ attitudes about foreign language learning.